2020
DOI: 10.36524/ric.v6i3.857
|View full text |Cite
|
Sign up to set email alerts
|

Tamanho Ótimo De Parcela Experimental Para Avaliar Características Físico-Químicas De Café Árabica

Abstract: A cadeia produtiva do café no Brasil apresenta grande importância socioeconômica, gerando divisas, com grande capacidade geradora de empregos, que segundo o primeiro levantamento da safra de 2020 da Conab, o país deverá colher entre 57,15 e 62,02 milhões de sacas beneficiadas de café. Já no Estado do Espírito Santo, a produção prevista pela CONAB encontra-se entre 13,02 milhões e 15,44 milhões de sacas beneficiadas, sendo 30,84% desta de café arábica. A pesquisa na cafeicultura tem contribuído para o desenvolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Studies have shown decreasing estimates of Xo in the following order: QRP, LRP and MMC (Silva et al, 2012;Moreira et al, 2016;González et al, 2018;Guimarães et al, 2019;Cargnelutti et al, 2021a,b); higher estimates of Xo by QRP compared to LRP (Peixoto et al, 2011); and higher estimates of Xo by LRP compared to MMC (Brito et al, 2012;Leonardo et al, 2014;Guarçoni et al, 2017;Sousa et al, 2018;Brioschi et al, 2020). Therefore, in these studies with the approach of comparing methods to determine the optimal plot size, results similar to those of the present study were found.…”
Section: (%)mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown decreasing estimates of Xo in the following order: QRP, LRP and MMC (Silva et al, 2012;Moreira et al, 2016;González et al, 2018;Guimarães et al, 2019;Cargnelutti et al, 2021a,b); higher estimates of Xo by QRP compared to LRP (Peixoto et al, 2011); and higher estimates of Xo by LRP compared to MMC (Brito et al, 2012;Leonardo et al, 2014;Guarçoni et al, 2017;Sousa et al, 2018;Brioschi et al, 2020). Therefore, in these studies with the approach of comparing methods to determine the optimal plot size, results similar to those of the present study were found.…”
Section: (%)mentioning
confidence: 99%
“…The values of CV (X) as a function of X can be related by the methods of modified maximum curvature (MMC) (Meier & Lessman, 1971), linear response and plateau model (LRP) (Paranaíba et al, 2009) and quadratic response and plateau model (QRP) (Peixoto et al, 2011), and make it possible to determine the optimal plot size (Xo) and the coefficient of variation in the optimal plot size (CV Xo ). Comparative studies involving the MMC and LRP methods have been carried out with papaya (Brito et al, 2012), pineapple (Leonardo et al, 2014), cabbage (Guarçoni et al, 2017) and cassava (Sousa et al, 2018), the LRP e QRP methods with passion fruit (Peixoto et al, 2011) and MMC, LRP and QRP methods with radish (Silva et al, 2012), sweet potato (González et al, 2018), cactus pear (Guimarães et al, 2019), coffee (Moreira et al, 2016, Brioschi et al, 2020, millet + slender leaf rattlebox + showy rattlebox (Cargnelutti et al, 2021a) and buckwheat (Cargnelutti et al, 2021b), evidencing distinct results between the methods and the importance of using more than one method to determine the optimal plot size.…”
Section: Introductionmentioning
confidence: 99%